Social equity in the data era: A systematic literature review of data‐driven public service research. (29th December 2022) - Ruijer, Erna; Porumbescu, Gregory; Porter, Rebecca; Piotrowski, Suzanne
Abstract: Governments increasingly rely on large amounts of data to deliver public services. In response, there is a robust discussion about the implications of this trend for efficiency and economy, but much less attention is paid to social equity. To address this issue, our study synthesizes cross‐disciplinary research on the relationship between data‐driven public services and social equity. Based on a systematic literature review of 190 articles covering a decade of research, we demonstrate how public sector data applications relate to social equity in terms of access to services, treatment, service quality, and outcomes. Our review identifies key mechanisms related to data collection, storage, analysis, and usage that need to be addressed to ensure more equitable data‐driven public services. This review contributes to public administration research and practice by highlighting the complexities of social equity in the data era.